2020
DOI: 10.1002/adhm.201901713
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulating and Deciphering Tumor Microenvironment by Using 3D Printed Plastic Brick–Like Microfluidic Cell Patterning

Abstract: Within the body, tumor cells are surrounded by neighboring counterparts, such as extracellular matrix, vasculature, and host stroma, which is also known as the tumor microenvironment. To understand tumorigenesis, it is essential to reconstitute the incorporative tumor niche with quantitative measurements in vitro. Here, a 3D printed plastic brick–like microfluidic gadget is developed for spatially patterning tumors and fibroblasts, enabling the recapitulation of tumor microenvironment with minimized microfluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…In a study involving tumors and fibroblasts for a developing tumor micro-environment with a microfluidic channel, a 3D printed plastic brick-like microfluidic gadget was fabricated, which effectively involves heterotypic co-culturing and aids in phenotype decoding and molecular assays. The data obtained were validated using a mouse xenograft model and it was found that the 3D in vitro method helps in the understanding of tumorigenesis and the associated tumor micro-environment [136]. A 3D bioprinted GelMA/PEGDA hybrid scaffold mimicked the tumor micro-environment of human malignant melanoma cell and was reported to be suitable for the expansion and differentiation of tumor cells; additionally, tumor cells were growing faster and exhibited drug-resistant potential [137].…”
Section: Tumor Microenvironment and 3d Printingmentioning
confidence: 92%
“…In a study involving tumors and fibroblasts for a developing tumor micro-environment with a microfluidic channel, a 3D printed plastic brick-like microfluidic gadget was fabricated, which effectively involves heterotypic co-culturing and aids in phenotype decoding and molecular assays. The data obtained were validated using a mouse xenograft model and it was found that the 3D in vitro method helps in the understanding of tumorigenesis and the associated tumor micro-environment [136]. A 3D bioprinted GelMA/PEGDA hybrid scaffold mimicked the tumor micro-environment of human malignant melanoma cell and was reported to be suitable for the expansion and differentiation of tumor cells; additionally, tumor cells were growing faster and exhibited drug-resistant potential [137].…”
Section: Tumor Microenvironment and 3d Printingmentioning
confidence: 92%
“…However, the conventional 3D models cannot truly mimic the complex TME, thus are inadequate for understanding the role of fibroblast cells in metastasis process [27]. A 3D printed brick like cell patterning microfluidic platform was developed for studying the effect of tumor cells on fibroblasts through co-culturing process [26]. The study showed that almost all fibroblast cells converted to an intermediate state between normal and CAFs, which was associated with hyperactivity of ribosome biogenesis.…”
Section: Influence Of Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…Deep data mining combined with in vivo results indicated that both the tumor cells and fibroblasts crucially impacted each other. While the HT1080 cells converted the fibroblasts to CAFs, the surrounding fibroblasts controlled the spread of fibrosarcoma cells at the initial stage of metastasis [26]. Another microwell array-based microfluidic platform was designed to elucidate how tumor spheroids invade in the presence of fibroblasts.…”
Section: Influence Of Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%